Seasonal Patterns of Oestrus and Reproduction in Street Dogs of Indian Cities - Brill, George; Kartal, Tamara; Yadav, Dev Prakash; Bhyan, Mukesh; Patel, Chirag; Sheoran, Shiv Kumar; Patel, Piyush; Painuly, Bimmy; Chaudhari, Amit (Frontiers in Veterinary Science, 2022)
Understanding seasonal breeding dynamics is essential for maximizing efficiency and welfare in the application of street dog management programs. Humane Society International (HSI) has conducted many animal birth control programmes concerning the street dog populations in urban India. This paper analyses the data on reproductive indicators—oestrus, pregnancy, and pups—collected by HSI sterilisation clinics in the cities of Jamshedpur, Dehradun, and Vadodara over a period of 3, 5 and 4 years, respectively. We found a consistent reproductive seasonality dynamic in all three cities, with peak oestrus and pregnancies occurring in the late/post-monsoon season. Pup proportions peaked soon after. Both these findings are consistent with previous studies of free-roaming domestic dog populations both in India and worldwide. Additionally, we identified minor inter-city differences in the temporal breeding dynamic, which we propose are the result of localised seasonal climatic and human factors. Finally, we examine and assert the relevance of breeding seasonality in the implementation of efficient and welfare-sensitive birth control programmes.